Characteristics of the Japanese national team of the First Youth Olympic Games - Tanabe, Y.; Asakawa, S.; Arakida, Y.; Kono, I.; Akama, T. (Journal of Sports Medicine & Doping Studies, 2015)
Objective: To investigate the change in young elite Japanese athlete`s attitudes during the Youth Olympic Games (YOG) in 2010.